Acoustic stimuli from predators trigger behavioural responses in aggregate caterpillars. (15th April 2019) - Breviglieri, Crasso Paulo B.; Romero, Gustavo Q.
Abstract: Prey detect their predators through predator signals and cues and, consequently, respond with anti‐predatory behaviours to inhibit the action of their aggressors. Lepidopterans can intercept signals emitted by predators and may defend themselves through chemical, morphological or behavioural responses. In this study, we investigated the effect of acoustic stimuli of different predators on defensive behaviour of gregarious caterpillars. Our results demonstrated that Hylesia nigricans (Lepidoptera, Saturniidae) caterpillars alter their behaviour (i.e. abruptly raising the head) in response to the acoustic stimulus of the predators (i.e. predation risk signals from birds and wasps). The magnitude of this response depended on predator identity and caterpillar body size. Larger caterpillars responded more strongly to predatory stimuli than smaller caterpillars. However, regardless of the size of the caterpillars, they responded more strongly to the stimuli of wasps. In addition, we identified that H. nigricans caterpillars emit ultrasonic noise after detecting the stimuli of the predators – this noise seems to function as an alert about the risk of predation during the early stages of development (second and fifth instars). The duration of ultrasonic emission (i.e. milliseconds) increases with the number of repetitions of the stimuli (i.e. wing‐beat sounds of the wasps and insectivorous birds). These results provide novel information about predation risk in interactions among caterpillars and their predators, and indicate possible communication among invertebrates mediated by the risk of predation. Abstract :